Determinan Masalah Gizi Remaja di Pondok Pesantren Tebuireng (Studi Kualitatif) - Niken Widyastuti Hariati (Jurnal Ilmiah Kesehatan (JIKA), 2021)
Adolescents are a strategic target in community nutrition improvement efforts, where adolescent nutrition problems are complex nutritional problems. This study aimed to examine the determinant factors that affect the nutritional problems of students at Pondok Pesantren Tebuireng, Jombang, East Java. This research used qualitative approach of phenomenology paradigm. Informants as many as 12 people were determined purposively. Data were collected through in-depth interviews and observations. Validation of data by triangulation method, processed and analyzed by content analysis and presented in narrative form. The research indicated that the nutrition problem among the students of Tebuireng Islamic Boarding School are not only skinny but also fat even obese in terms of their nutrition status. The determinant factors of nutriton problem among the students with fat nutrition status related to eating habit and activity habit are the lack of physical activity (excercise) because of minimum facilities, consuming food with high fat and sugar as it is easy to get around the boarding school, irreguler breakfast and dinner eating habit due to activity levels (schedule), the lack of knowladge on health eating habit, perception on body image, and a habit of consuming low number of vegetables related to taste. Meanwhile, the determinant factors of nutrition problem among the student with skinny nutrition status related to eating habit and activity habit are irreguler breakfast eating habit due to activity levels, low daily intake due less appetite, and low level of knowledge on healthy eating habit.